Maintaining The Status of Hydration on Mr. G With Pneumonia in Fatmawati Hospital - Aat Djanatunisah; Riri Maria (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Pneumonia is a health problem in the world with a high mortality rate both in developing countries and in developed countries such as America, Canada and European countries. In Indonesia, the number three cause of death after cardiovascular disease and tuberculosis. Low socioeconomic factors increase mortality. This infection is generally spread from someone who is exposed in the neighborhood or has direct contact with infected people through their hands or by breathing air (droplets) due to coughing or sneezing. In the pandemic era, pneumonia is very feared because it is related to respiratory diseases which are becoming a trend and issue, so it requires special treatment in this case. This case report aims to improve the provision of nursing care for pneumonia patients to mantaining hydration status with airway clearance problems. Nursing assessment of pneumonia patients was carried out on September 13, 2020, a 52-year-old man who has a history of DM and smoking comes with complaints of coughing but no phlegm, fever since one week ago has disappeared, the patient has diarrhea since 2 days before entering the house pain and stomach pain, the patient also has nausea and vomiting and has no appetite. Nursing intervention for 3 days in accordance with the established outcome criteria. From the nursing intervension carried out, the problem of clearing the airway was resolved, marked by no coughing, normal breathing, no ronchi, moist mucosa and no cyanosis. Nursing intervention to maintaining the patient's adequate hydration status can overcome the problem of ineffective airway clearance.